Guinea - Joint World Bank-IMF Debt Sustainability Analysis Update : August 2019 - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Guinea is at moderate risk of external debt distress with some space to absorb shocks. All external debt burden indicators under the baseline scenario lie below their policy-dependent thresholds. Stress tests suggest that debt vulnerabilities will increase if adverse shocks materialize. Under the most extreme stress tests, all solvency and liquidity indicators breach their thresholds for prolonged periods. The overall risk of public debt distress is also assessed to be moderate, with the application of judgement regarding a brief and marginal breach for the PV of total public debt to GDP ratio over 2019-20, reflecting the one-off impact of the recapitalization of the central bank. Guinea’s external and public debt position at end-2018 improved compared to the December 2018 DSA, owing to upward revisions of growth estimates in 2016–17, lower-than-anticipated external loan disbursements in 2018, and a stable exchange rate in 2018. A prudent external borrowing strategy aimed at maximizing the concessionally of new debt, limiting non-concessional loans to programmed amounts and strengthening debt management will be key to preserving medium-term debt sustainability.